Tissue factor gene expression in the adipose tissues of obese mice - Samad, Fahumiya (The National Academy of Sciences, 1998)
Altered expression of proteins of the fibrinolytic and coagulation cascades in obesity may contribute to the cardiovascular risk associated with this condition. We previously reported that plasminogen activator inhibitor 1 (PAI-1) is dramatically up-regulated in the plasma and adipose tissues of genetically obese mice. This change may disturb normal hemostatic balance and create a severe hypofibrinolytic state. Here we show that tissue factor (TF) gene expression also is significantly elevated in the epididymal and subcutaneous fat pads from ob/ob mice compared with their lean counterparts, and that its level of expression in obese mice increases with age and the degree of obesity. Cell fractionation and in situ hybridization analysis of adipose tissues indicate that TF mRNA is increased in adipocytes and in unidentified stromal vascular cells. Transforming growth factor β (TGF-β) is known to be elevated in the adipose tissue of obese mice, and administration of TGF-β increased TF mRNA expression in adipocytes in vivo and in vitro. These observations raise the possibility that TF and TGF-β may contribute to the increased cardiovascular disease that accompanies obesity and related non-insulin-dependent diabetes mellitus, and that the adipocyte plays a key role in this process. The recent demonstration that TF also influences angiogenesis, cell adhesion, and signaling suggests that its exact role in adipose tissue physiology/pathology, may be complex.